Elimination of Acquired Factor VIII Antibodies by Extracorporal Antibody-based Immunoadsorption (Ig-Therasorb®) - Knöbl, P; Derfler, K; Korninger, L; Kapiotis, S; Jäger, U; Maier-Dobersberger, T; Hörl, W; Lechner, K; Pabinger, I (Thrombosis and Haemostasis, 1995)
Treatment of potent factor VIII antibodies is a difficult problem. In some cases a reduction ofthe antibody titer is necessary for effective treatment with human factor VIII concentrates. We describe a new method for extracorporal eliminationof factor VIII antibodies (antibody-based immunoadsorption). Blood is drawn from an antecubital vein, citrated, and plasma is separated with a rotating membrane. Plasma passes alternately through one of two columns filled with sepharose-coupled polyclonal sheep antibodies to human immunoglobulins (Ig-Therasorb00), whereas the other column is regenerated. Each cycle has a duration of 15 min. Three patients with high titer factor VIII antibodies (one hemophiliac and 2 with spontaneous antibodies; titers 29, 132, and 313 BU/ml, respectively) were treated. The average reduction of the antibody titer was 76.1 ± 17.2% per session. In each patient 4 sessions were necessary to reduce the antibody titer to < 1 BU/ml. The mean processed plasma volume was 6731 ± 640 ml and the mean duration of each session 3.9 ± 0.7 h. Serum IgG, IgA and IgM levels decreased by 75.3 ± 11.9%, 62.9 ± 19.1%, and 54.8 ± 23.8% respectively. The procedure was tolerated without any side effects. Thus, rapid elimination of factor VIII inhibitors can be achieved with antibody-based immunoadsorption, which can be lifesaving in some cases. This promising method should be evaluated in a larger number of patients.